Examining the Effectiveness of the Fathers and Babies Intervention: A Pilot Study - Tandon, S. Darius; Hamil, Jaime; Gier, Emma E.; Garfield, Craig F. (Frontiers in Psychology, 2021)
There is increasing recognition of the importance of addressing the mental health of fathers, including during the perinatal period. Fathers exhibiting mental health concerns during the perinatal period are at heightened risk for future negative mental health outcomes and are less likely to engage in nurturing relationships with their children, leading to a sequalae of negative child outcomes during infancy and into adolescence. Although interventions have been developed for perinatal fathers, they typically do not focus directly on addressing paternal mental health. To fill this gap, we developed the Fathers and Babies intervention to be delivered to perinatal fathers whose partners (mothers) were enrolled in home visiting programs. A pre-post longitudinal study was conducted in which 30 father-mother dyads were recruited from home visiting programs. Fathers received the 12-session Fathers and Babies intervention while the mother concurrently received the Mothers and Babies intervention delivered to her by a home visitor. Baseline, 3-month, and 6-month self-report surveys were conducted with both fathers and mothers. Fathers and mothers had statistically significant decreases in perceived stress between baseline and both follow-up time points, with moderate effect sizes generated for both sexes. No statistically significant differences were found for depressive symptoms, anxiety symptoms, or perceived partner support, although we found small effects for reductions in depressive symptoms among fathers, as well as increases in the percentage of fathers and mothers who reported high levels of emotional and instrumental support post-intervention. While preliminary, these findings suggest the potential for Fathers and Babies to positively impact the mental health of fathers in the perinatal period, and also signal the viability of home visiting as a setting for delivering this intervention. Future research should employ a comparison group to generate stronger evidence of intervention effectiveness and include measurement of dyadic relationships and paternal parenting practices.